Evaluative conditioning depends on higher order encoding processes - Fiedler, Klaus; Unkelbach, Christian (Cognition & emotion, 2011)
Evaluative conditioning (EC) is commonly conceived as stimulus-driven associative learning. Here, we show that internally generated encoding activities mediate EC effects: Neutral conditioned stimuli (CS) faces were paired with positive and negative unconditioned stimuli (US) faces. Depending on the encoding task (Is CS a friend vs. enemy of US?), Experiment 1 yielded either normal EC effects (CS adopting US valence) or a reversal. This pattern was conditional on the degree to which encoding judgements affirmed friend or enemy encoding schemes. Experiments 2a and 2b replicated these findings with more clearly valenced US faces and controlling for demand effects. Experiment 3 demonstrated unconditional encoding effects when participants generated friend or enemy relations between CS and US faces. Explicitly stated friend or enemy relations in Experiment 4 left EC effects unaffected. Together, these findings testify to the importance of higher order cognitive processes in conditioning, much in line with recent evidence on the crucial role of conditioning awareness.
Published online: 05 Oct 2010
Gesehen am 09.05.2022